Perlindungan Penanaman Modal Asing dan Pengaruh Pertembuhuan Ekonomi Berdasarkan Neo-Classical Economy Theory - Rotua F N Simanjuntak; Naomi Olivia Br Manurung; Hasyim Hasyim; Riski Daulay; Lany Situmorang (HEMAT: Journal of Humanities Education Management Accounting and Transportation, 2024)
Foreign investment is a leading sector and provides many benefits for the welfare of society. Investment in the tourism sector, especially the hotel sector, is wide open to foreign investors, both full ventures and joint ventures. This research uses normative juridical legal research methods. Regulations regarding Foreign Investment (PMA) in Indonesia are currently in Law Number 25 of 2007 concerning Capital Investment (UUPM) with several amendments through Law Number 11 of 2007 of 2020 on Job Creation. At the time of its birth, the UUPM was considered a breakthrough which was born as a new law and included domestic investment legislation (PMDN). Safe investments require legal protection from the government so that they can be run with a better business plan. Government policies that support investors towards investment security will be a big attraction for investing in Indonesia. To attract investors who want to invest their capital, it is necessary to build a supportive environment, work opportunities and permits that can be mutually beneficial. It can be concluded that politics has a big influence on the entry of foreign investors